Effectiveness of Steamed Sweet Potato on Upper Arm Circumference of Pregnant Women with Chronic Energy Deficiency (Chd) in Lingga Village, West Kalimantan - Rachmaida, Arlina; Fajrin, Dessy Hidayati; Lubis, Shelvia Melini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Pregnant women with low nutritional status tend to give birth to children with developmental and growth problems. Therefore, pregnant women with Chronic Energy Deficiency need intervention, especially by midwives. In 2023, the number of pregnant women in the first trimester was 20. Some studies suggest that milk and local foods such as sweet potatoes can be an alternative choice. To determine the effectiveness of increasing the Upper Arm Circumference (MUAC) for pregnant women with Chronic Energy Deficiency (CED) after being given PMT in the form of steamed sweet potatoes and milk. The study used a quasi-experimental design for one month. The total population is 20 respondents, and using the total sampling technique, 10 people get steamed sweet potatoes and 10 people get milk. The study used a Pre-Experimental Design with the One-Group Pretest-Posttest Design type. There were differences in the size of the Upper Arm Circumference (MUAC) of CED pregnant women before and after being given steamed sweet potatoes and milk, with a p-value of 0.000 <0.05. There is no difference in effectiveness between giving steamed sweet potatoes and milk to pregnant women with Chronic Energy Deficiency (CED) in Lingga Village, Kubu Raya Regency, with a p-value of 0.062 (p > 0.05). Giving milk to pregnant women is more effective in increasing the Upper Arm Circumference (LiLA) of pregnant women with Chronic Energy Deficiency (KEK) in Lingga Village, Kubu Raya Regency, with a median difference in the median value of giving milk to pregnant women of 1.06 and steamed sweet potatoes of 0.50.